Water Storage Index Estimation using Geographic Information System - Agus Wuryanta; Ugro Hari Murtiono (Universitas Muhammadiyah Surakarta, 2014)
The study aims to estimate water storage index (IPA) of six sub watersheds (Panjang, Rengas, Legi, Galeh, Parat, and Sraten) in the cachment area of Rawapening lake by using Geographic Information System. Water storage index can be calculated from average discharge (m3) devided by water requirement (m3) for each land cover/land use. Landuse information is obtained from Indonesian Topographic Map scale of 1:25.000 as updated by using SPOT image (2006), while surface water availability data was obtained from the ministry of public works. The results indicate that 1) IPA of Panjang Subwatershed was categorized as good condition with an index value of 1,49; 2)IPA of Rengas and Legi sub watersheds were categorized as moderate condition with index value 0,76 and 0,55; 3) IPA of Galeh, Parat, and Sraten sub watersheds was categorized as bad with index value of 0,3, 0,15, and 0,33, this watershed need to be improved especially an effective water resources plan, allocating and distributing of water according to priority establishment.